GLACIAL AND INTERGLACIAL PERIODS OF SIBERIA: PALEOCLIMATE RECORD OF LAKE BAIKAL AND CORRELATION WITH WEST SIBERIAN STRATIGRAPHIC SCHEME (THE BRUNHES CHRON) - Karabanov E.B.; Prokopenko A.A.; Kuz'min M.I.; Williams D.F.; Gvozdkov A.N.; Kerber E.V. (My University, 2001)
The article presents a new Lake Baikal paleoclimate record of biogenic silica for the Brunhes Chron (from 780 ka ago to the present). Correlation of the Lake Baikal record with the marine oxygen isotope record shows that climatic changes of Central Eurasia are not specific but follow the pattern of global climate fluctuations of the Northern Hemisphere caused by orbital forcing. Specific features of continental climatic changes (glaciations during substages 5d, 7d, 9d, and 15bcd) were also found in the Baikal record. Correlation of paleoclimate record of biogenic silica from Baikal bottom sediments with Siberian stratigraphic scheme was made for the Brunhes Chron. The paleoclimatic events of Lake Baikal are well identified with marine oxygen isotope stages and correlate well with climatic events of Siberian stratigraphic schemes for the Late Pleistocene but do not correlate for the Middle and Early Pleistocene. There are 10 warm interglacial and 9 cold glacial periods during the Brunhes Chron of Lake Baikal, which agree with marine records but disagree with the Siberian stratigraphic scheme having only 7 glacial and 8 interglacial periods within the Brunhes. This disagreement is probably related to the incomplete nature of terrestrial outcrop sections of Siberia. The new Lake Baikal record may provide an important chronostratigraphic base for Central Asia.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен